CONTINUOUS MODE OF HIGH INTENSITY ULTRASOUND THERAPY EFFECTS IN RATS SOFT TISSUES (Fiep Bulletin - online, 2014)
Today ultrasound therapy (UST) is being used in the treatment of both the musculo-squeletic and dermato-functional systems most diverse injuries based on its numerous positive effects. It has been two decades since treatments in relation to natural effects with scientific basis in the use of UST was suggested. OBJECTIVE: To investigate effects of high intensity ultrasound stimulation in continuous mode on rats morphological soft tissues. METHODS: The task was developed through experimental descriptive study with 15 female Wistar rats weighing between 170g -230g.The specimens were divided into a control group and 02 subgroups (B and B ), and submitted to a high intensity ultrasound stimulation in its 3 4 back area in continuous mode with a power of 2W/cm2 during 5 minutes. Parts of animals were processed for pigmentation using the hematoxiline-eosine method. As for the qualitative morphological analysis, optical microscopy was used. RESULTS: The control group show normal morphological characteristics. Parts of subgroups B and B used under ultrasound stimulation in 3 4 continuous mode presented a basophilic aspect compatible with cellular necrosis. CONCLUSION: Our study showed that high intensity ultrasound stimulation has strong side effects in continuous mode. This suggests that ultrasound high dosages should not be used and the treatment of high inflammatory processes, because they can have dangerous side effects.
Keywords: Ultrasound therapy; Side Effects; Tissues